Glucose receptor deletion and engineering : Impact on xylose sensing and utilization in Saccharomyces cerevisiae - Bolzico, Bruna C.; Persson, Viktor C. ; 0000-0001-8763-0993; Comelli, Raul N.; Gorwa-Grauslund, Marie (FEMS Yeast Research, 2025)
Unlike glucose, the sub-optimal xylose utilization in recombinant Saccharomyces cerevisiae strains may stem from an unusual signaling response that is not adapted to detecting xylose as a fermentable substrate. We hypothesize that the membrane receptor Snf3p, known for sensing extracellular low glucose levels, may contribute to xylose recognition. To test this, we explored the effect of SNF3 inactivation and overexpression by measuring the response of the HXT2p-GFP biosensor integrated into S. cerevisiae strains with heterogeneous xylose assimilation and metabolism capacities. We showed that the absence of SNF3 effectively reduced HXT2p induction, while its overexpression improved signaling in the presence of xylose, suggesting the involvement of the receptor in the extracellular detection of this sugar. Although we attempted to engineer a xylose sensing system based on a chimeric receptor, its integration did not lead to considerable improvements in signal activation, indicating the need for further investigation. Finally, we showed that triggering the Snf3p pathway impacted xylose metabolism, with altered receptor levels prompting shifts in both biomass production and metabolite accumulation. Our findings suggest that understanding xylose sensing and its metabolic connection is essential for promoting more efficient xylose utilization in S. cerevisiae, a key step toward optimizing industrial bioprocesses.
Keywords: GFP-based biosensor; Hxt2p; receptor engineering; saccharomyces cerevisiae; Snf3p; sugar signaling; xylose